Implementation of Islamic Inheritance Law: Study of History, Law and Its Principles - Irfan Abdurahman; Asep Lukman Daris salam; Parhan Taqwa Ali Hasan (Penerbit Hellow Pustaka, 2024)
Islamic inheritance plays a pivotal role in Islamic teachings, holding significant importance. Within certain Muslim societies, conflicts often emerge among heirs regarding the distribution of inheritance. Consequently, it becomes imperative for the Muslim community to comprehend the intricacies of inheritance in Islam. This study conducts a literature review to delve into the subject matter. The authors gather data through a comprehensive search of various books, articles, and scholarly works. The findings of the study elucidate the extensive historical practice of Islamic inheritance, dating back to pre-Islamic times and the revelation of the Qur'an. In the practical implementation of Islamic inheritance, it becomes essential to understand the legal framework, principles, and related aspects such as pillars, conditions, causes, and barriers.